Hyperkinetic Movement Caused by Diabetic Striatopathy: A Case Report (Bangladesh Journal of Medicine, 2025)
Hyperkinetic movement like chorea is rare in uncontrolled diabetic patients. Increased level of glucose affects the basal ganglia known as diabetic striatopathy. Synonym of this condition includes hemichorea-hemiballismus, chorea-hyperglycemia-hemiballismus syndrome, non-ketotic hyperglycemic hemichorea. We report a 65-year-old woman with uncontrolled diabetes who presented with unintentional ballistic movements of his right upper and lower extremities making her disabled. Magnetic resonance imaging of her brain demonstrated findings suggestive of diabetic striatopathy. Antipsychotics (eg. Haloperidol) helped to control her chorea-like movements. Strict glycemic control was advised to prevent recurrence.Bangladesh J Medicine 2025; 36(2): 136-138